PENGEMBANGAN FRONT END PADA SISTEM INFORMASI UJI KOMPETENSI PADA LEMBAGA SERTIFIKASI KOMPETENSI POLITEKNIK CALTEX RIAU - Zulvi, Mutia sari; Mufidah, Nur; Rizky Mirza, Junaldo; Agustina, Dea (Jurnal Komputer Terapan, 2024)
Politeknik Caltex Riau (PCR) is one of the private vocational colleges in Pekanbaru City, Riau, which was established in 2001. Every year PCR holds certification for prospective graduates, where this certification is mandatory for prospective graduates as a graduation requirement. To facilitate prospective graduates, PCR has a Professional Certification Institute (LSP). This certification is used to ensure that graduates have competencies in accordance with their field of expertise before entering the workforce. PCR already has an LSP-P1 system. LSP P1 is a 1st party professional certification institution formed by educational institutions. The existing system is only at the registration stage, while other administrative files are collected in paper / hard file form. The impact is that some files are lost, and it takes a long time to process the data. The resulting solution is to design the Front End of the LSP System including the registration section, assessment process, determination of results, appeals against certification decisions and complaints. The design uses the Design Thinking method on the Front-End side. Based on the test results using UEQ, which reached an excellent scale (percentage above 2% with a range of -1 to 2.5%) in terms of Attractiveness, Clarity, Efficiency, and Novelty of system design.